Feasibility Assessment of Construction 4.0 Technology Investment: Drones, Building Information Modeling (BIM) and Virtual Reality (VR) - Safira, Herdiana; Tanne, Yongki Alexander; Maarif, Muhamad Samsul (Faculty of Engineering, Universitas Negeri Yogyakarta, 2024)
Construction 4.0 technology is an anticipation of the challenges of quality improvement in the construction industry. However, its implementation has not been simultaneous with an evaluation of the benefits and value of investment. For this reason, this research evaluates the benefits and investment feasibility of construction 4.0 technology on 36 projects of the Indonesian construction state-owned enterprise (SOE), PT. XYZ Persero Tbk. during 2020-2022 for Drones, Building Information Modeling (BIM) and Virtual Reality (VR) as individually and integrated. Based on evaluation data on the use of technology and financial data from technology investments obtained, this research quantitatively calculates the value of the benefits of increasing productivity and then calculates the financial evaluation using the Return on Investment (ROI), Net Present Value (NPV), Internal Rate of Return (IRR) and Benefit-Cost Ratio (BCR) methods and implies those results qualitatively. As a result, individually, BIM is the technology that contributes the most in terms of benefits, VR contributes well in terms of investment value, while drones still have development potential. Integration between technologies is still challenging where the use of technology simultaneously does not guarantee significant integration between the three technologies reviewed in this research.